Resistance and negotiation in translating religious identity: A study on the Arabic translation of Gadis Kretek - Muhamad Saiful Mukminin; Sajarwa (Diwan: Jurnal Bahasa dan Sastra Arab, 2025)
The difference in religious cultural backgrounds encourages translators to make efforts to resist and negotiate when translating religious terms in literary works. Resistance focuses on preserving the original meaning, while negotiation adjusts the meaning to align with the target culture's understanding. Based on that translation strategy, this study analyzes the resistance and negotiation of religious identity in translating the novel Gadis Kretek into Arabic. Using a qualitative method with interpretative-comparative analysis, this research examines the religious identity in both the source and target texts, particularly through linguistic units representing religious terms. The data was taken from the novel Gadis Kretek and its Arabic translation Fatātu al-Sajāir. Data was collected by identifying religious terms in the texts, categorizing them according to an existing framework, and comparing their translations. The analysis focuses on the patterns of resistance and negotiation in translating these terms. The results reveal two primary patterns in the translation of Gadis Kretek. First, resistance, where religious terms are maintained in their original form or translated literally to preserve their sacredness. Second is negotiation, where adjustments are made to ensure the religious terms align with the target audience’s cultural understanding. Resistance is influenced by the similarity of belief systems between Indonesian Islam and Arab Islam, while negotiation arises due to differences in cultural contexts. These findings contribute to understanding religious translation in multilingual Islamic contexts and offer strategies for culturally sensitive translation practices. This study concludes that translation serves as a cultural bridge, preserving the core meaning while adjusting it to the target context.